1971
DOI: 10.1172/jci106761
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin excretion in rats with normal and impaired bilirubin conjugation: effect of phenobarbital

Abstract: A B S T R A C T The effect of phenobarbital on bilirubin excretion was studied in rats with different capacities for bilirubin conjugation. Drug treatment induced substantial increases in bilirubin UDP-glucuronyl transferase activity in the liver of both normal and heterozygous Gunn rats, but not homozygous Gunn rats in which enzyme activity is completely absent. However, enhancement of bilirubin excretion in vivo was observed only in heterozygous Gunn rats. In these animals the maximum capacity to excrete bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…Although the heterozygous animals did not usually manifest hyperbilirubinemia of such magnitude as the homozygous rats, the wide range of standard deviations in the former group bear out heterogeneity of genetic expression in these ani mals. The liver weight to body weight ratios in the Gunn rats were significantly lower than the Wistar controls as has been reported previously (23). Levels of protein (table II) in whole microsomes and smooth microsomes did not differ significantly in the three groups of animals.…”
Section: Plasma Bilirubin Liver Weight and Drug Metabolismsupporting
confidence: 78%
“…Although the heterozygous animals did not usually manifest hyperbilirubinemia of such magnitude as the homozygous rats, the wide range of standard deviations in the former group bear out heterogeneity of genetic expression in these ani mals. The liver weight to body weight ratios in the Gunn rats were significantly lower than the Wistar controls as has been reported previously (23). Levels of protein (table II) in whole microsomes and smooth microsomes did not differ significantly in the three groups of animals.…”
Section: Plasma Bilirubin Liver Weight and Drug Metabolismsupporting
confidence: 78%
“…In addition, we investigated the direct conversion of BMG to BDG by rat liver microsomes and evaluated the effect of pretreating the animals with phenobarbital to enhance hepatic conjugating ability (21). We found that rat liver microsomes contain a UDP-glucuronic acid-dependent enzyme system that converts bilirubin or BMG to BDG and that the activity of this enzyme system is enhanced by pretreatment of the animals with phenobarbital.…”
mentioning
confidence: 99%
“…Treatment with TCDD caused a 16-fold increase in benzo[a]pyrene hydroxylase activity, from 0.5 ± 0.1 to 8.2 i 0.9 ,umol of phenols formed per g of liver per hr (P < 0.001). By contrast, no bilirubin-UDPglucuronate transferase activity was detected in either control or TCDDtreated animals (1,9). DISCUSSION This paper reports successful chemical stimulation of the alternate pathways of bilirubin catabolism in the jaundiced Gunn rat.…”
mentioning
confidence: 67%
“…To explain this lack of response to phenobarbital, it has been assumed that the Gunn rats and the patients lack the genetic information necessary for synthesis of bilirubin-UDPglucuronate transferase (6)(7)(8)(9) and that the alternate pathways of bilirubin metabolism are not mediated by the mixed-function monooxygenases that respond to treatment with phenobarbital (9,10). Because phenobarbital induces preferentially the cytochrome P4W system (11,12), we have treated jaundiced Gunn rats with 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), the most potent known inducer of microsomal cytochrome P448 (P1450) (13), to determine its effect on metabolism of unconjugated bilirubin.…”
mentioning
confidence: 99%